Fine Particulate Air Pollution and Daily Mortality. A Nationwide Analysis in 272 Chinese Cities - Chen, Renjie; Yin, Peng; Meng, Xia; Liu, Cong; Wang, Lijun; Xu, Xiaohui; Ross, Jennifer A.; Tse, Lap A.; Zhao, Zhuohui; Kan, Haidong; Zhou, Maigeng (American journal of respiratory and critical care medicine, 2017)
Evidence concerning the acute health effects of air pollution caused by fine particulate matter (PM ) in developing countries is quite limited. To evaluate short-term associations between PM and daily cause-specific mortality in China. A nationwide time-series analysis was performed in 272 representative Chinese cities from 2013 to 2015. Two-stage Bayesian hierarchical models were applied to estimate regional- and national-average associations between PM concentrations and daily cause-specific mortality. City-specific effects of PM were estimated using the overdispersed generalized additive models after adjusting for time trends, day of the week, and weather conditions. Exposure-response relationship curves and potential effect modifiers were also evaluated. The average of annual mean PM concentration in each city was 56 μg/m (minimum, 18 μg/m ; maximum, 127 μg/m ). Each 10-μg/m increase in 2-day moving average of PM concentrations was significantly associated with increments in mortality of 0.22% from total nonaccidental causes, 0.27% from cardiovascular diseases, 0.39% from hypertension, 0.30% from coronary heart diseases, 0.23% from stroke, 0.29% from respiratory diseases, and 0.38% from chronic obstructive pulmonary disease. There was a leveling off in the exposure-response curves at high concentrations in most, but not all, regions. The associations were stronger in cities with lower PM levels or higher temperatures, and in subpopulations with elder age or less education. This nationwide investigation provided robust evidence of the associations between short-term exposure to PM and increased mortality from various cardiopulmonary diseases in China. The magnitude of associations was lower than those reported in Europe and North America.